Investigation of Malaysian low earth orbits for remote sensing applications - Okasha, Mohamed Elsayed Aly Abd Elaziz; I, Shuib; Mahmoud Idres, Moumen Mohammed (Institute of Physics Publishing, 2017)
This paper explores the orbit design procedures of a low Earth satellite orbit for remote sensing mission. The mission objective is to gather images over Malaysia as an area of interest for a variety of applications such as land monitoring and digital mapping. The design procedures are mainly driven by the payload performance, lighting conditions and the coverage requirements. Standard CubeSat platform with a NanoCam is considered for the mission. Numerical investigations show the trade studies of various satellite orbital parameters and their impact on the performance. The orbital parameters are optimized to meet the mission design requirements.